Functional role of movement and performance variability: Adaptation of front crawl swimmers to competitive swimming constraints - Escobar, D. S.; Hellard, P.; Pyne, D. B.; Seifert, L. (Journal of Applied Biomechanics, 2018)
To study the variability in stroking parameters between and within laps and individuals during competitions, we compared and modeled the changes of speed, stroke rate, and stroke length in 32 top-level male and female swimmers over 4 laps (L1-L4) in 200-m freestyle events using video-derived 2-dimensional direct linear transformation. For the whole group, speed was greater in L1, with significant decreases across L2, L3, and L4 (1.80 ± 0.10 vs 1.73 ± 0.08; 1.69 ± 0.09; 1.66 ± 0.09 · s-1, P < .05). This variability was attributed to a decrease in stroke length (L2: 2.43 ± 0.19 vs L4: 2.20 ± 0.13 m, P < .05) and an increase in stroke rate (L2: 42.8 ± 2.6 vs L4: 45.4 ± 2.3 stroke · min-1, P < .05). The coefficient of variation and the biological coefficient of variation in speed were greater for male versus female (3.9 ± 0.7 vs 3.1 ± 0.7; 2.9 ± 1.0 vs 2.6 ± 0.7, P < .05) and higher in L1 versus L2 (3.9 ± 1.3 vs 3.1 ± 0.1; 2.9 ± 0.9 vs 2.3 ± 0.7, P < .05). Intra-lap speed values were best represented by a cubic (n = 38), then linear (n = 37) and quadratic model (n = 8). The cubic fit was more frequent for males (43.8%) than females (15.6%), suggesting greater capacity to generate higher acceleration after the turn. The various stroking parameters managements within lap suggest that each swimmer adapts his/her behavior to the race constraints.